Three-Dimensional Core-Branch α-Fe2O3@NiO/Carbon Cloth Heterostructured Electrodes for Flexible Supercapacitors - Zhang, Miao; Li, Xifei; Wang, Xiaohua; Li, Dejun; Zhao, Naiqin (Frontiers in Chemistry, 2020)
A convenient and scalable hydrothermal method was developed for the fabrication of the core-branch Fe2O3@NiO nanorods arrays directly grown on flexible carbon cloth (denoted as Fe2O3@NiO/CC). Such a unique architecture was applied as an electrode of the supercapacitors. As a result, the Fe2O3@NiO/CC exhibited a high areal capacitance 800 mF cm−2 at 10 mA cm−2, which was about 10 times increase with respect to Fe2O3 nanorods array grown on carbon cloth (Fe2O3/CC). The Fe2O3@NiO/CC also had the long life cycle (96.8 % capacitance retention after 16,000 cycles) and remarkable rate capability (44.0 % capacitance loss at a very large current density of 100 mA cm−2). The superior performance of the Fe2O3@NiO/CC should be ascribed to the reduction of the contact resistance and the free-standing structure of the flexible electrode. This study provides a novel strategy to construct high-performance flexible electrode materials with unique core-branch structure by incorporating two different pseudocapacitive materials.